Information security : 18th International Conference, ISC 2015, Trondheim, Norway, September 9-11, 2015, Proceedings /: 18th International Conference, ISC 2015, Trondheim, Norway, September 9-11, 2015, Proceedings. (2015) - Unknown
No abstract available